Lietuvių kalbos postpoziciniai vietininkai - Zinkevičius, Zigmas (Baltistica, 1982)
Postpositional locatives in LithuanianThe paper argues that postpositional locatives in Lithuanian (inessive, illative, adessive, allative) are not formations of the same epoch, but rather they were formed at different times; the process of their formation must have been long and continued right up to the appearance of the first Lithuanian printed book when the case-forms fell into a decline. First came singular forms, next – plural forms. More complicated and protracted was the development of inessive and adessive case-forms.Ā- and ē-stem sg. iness. and ill. forms (e. g. šakojè, žẽmėje, šakõn, žẽmėn) are considered to be the oldest. The other sg. ill. and particularly sg. iness. forms are products of later development, as they are, as a rule, constructed in the above-mentioned pattern. The paper gives a detailed analysis of the case-forms and on the basis of the analysis it argues that the singular of all postpositional locatives had already been formed and become stable by the beginning of the period of writing -nothing of the kind can be said of the plural. Only illative and allative possessed then stable plural forms.The development of pl. iness. and adess. forms was hindered by the residual ancient Indo-European locative in -su. The centre of the author's attention, however, is the interrelationship of the case-forms and particularly the origin and development of pl. iness. and adess. case-forms.On the basis of a detailed analysis of the old writings, the author argues that the pl. iness. šakosa derives not from šakose, as is generally assumed, but it presents by itself a transformed version of the older form šakosu. The form šakose is to be derived not from the pl. acc. * šakā́s + *éп, but it should be treated as a transform of šakosu от šakosa in -e from the sg. inessive, cf. šakojè. Pl. adess. šakosumpi is not a transform of šakosempi, as is generally assumed, but the older variant of the plural adessive, a variant derived from the old locative. Its subsequent variant is šakosampi and the newest – šakosempi.The paper also examines other problems relating to the history of postpositional locatives, e. g. the specificity of the development of the adessive of personal pronouns, the transformation of enclitic postposition into stressed in iness. and ill. case-forms, the reduction of the case-forms, etc. The paper shows in passing that 16th century Lithuanians pronounced most frequently the pl. adess. šakosempi as šakosémpi (with stress on e), not as šakósempi, as is generally assumed.
Keywords: lietuvių postpoziciniai vietininkai; morfologija; inesyvas; iliatyvas; adesyvas; aliatyvas